2017
DOI: 10.2298/ciceq150824002e
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of silver nanoparticles using Alcea rosea flower extract as a new generation of antimicrobials

Abstract: Green synthesis of silver nanoparticles (AgNPs) was developed by treating Ag+ with Alcea rosea flower extract. AgNO3 concentration, flower extract quantity, and reaction temperature were found to be significant factors in the bioreduction reaction. Synthesized AgNPs were almost spherical in shape with an average diameter of 7.2 nm. Fourier transform infrared spectroscopy (FTIR) analysis revealed that oxygen-bearing functional groups in the A. rosea flower extract are responsible for reduction of Ag+. The minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 39 publications
4
37
0
1
Order By: Relevance
“…In our previous investigations we found that 5 mM silver nitrate is the best concentration for green synthesis of AgNPs (Ebrahiminezhad et al, 2016e;2016b). So, in this experiment final concentration of silver nitrate was set to be 5 mM.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous investigations we found that 5 mM silver nitrate is the best concentration for green synthesis of AgNPs (Ebrahiminezhad et al, 2016e;2016b). So, in this experiment final concentration of silver nitrate was set to be 5 mM.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Silver nanoparticle (AgNPs) are one of the most studied and applied nanoparticles in medicine and biomedicine. These particles are well known as a potent antimicrobial against almost all bacterial strains (Ebrahiminezhad et al, 2016a;2016b;2016d). AgNPs are also effective against antibiotic resistant microorganisms and increase the efficiency of antibiotics (Devi and Joshi, 2012;Fayaz et al, 2011;Ruden et al, 2009;Shahverdi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nanostructures are now used in Magnetic Resonance Imaging (MRI), magnetic transfection, hyperthermia, DNA and cell labelling, tissue engineering, and targeted drug delivery [24][25][26][27][28][29][30][31][32][33][34]. Biosynthesized nanostructures are more interesting for these biomedical applications due to high biocompatibility and high physicochemical stability [35][36][37][38][39][40][41][42].…”
Section: Iron Reducing Bacteria and Iron Nanoparticlesmentioning
confidence: 99%